Students' Perception on Collaboration through the Online Implementation of Interprofessional Education (IPE) in Handling Covid-19 - Andhini, Citra Setyo Dwi; Fajriyani, Ika Nur; Kamasturyani, Yani; Marisa, Dewi Erna; Rahayu, Rosalia; Nurhaeni, Ani; Cahyati, Sri Nur (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Interprofessional education is Interprofessional education (IPE) entails learning with, from, and about each other to enable effective collaboration and improve health outcomes. Negative perception, professional egoism, bad knowledge about it will hamper collaboration. Reducing negative perception and creating readiness is a prime target for IPE training. COVID-19 restrictions necessitated wholesale scale conversion of curricula to online learning environments globally. The research is aimed at getting students' perceptions of collaboration through interprofessional education online. This was a descriptive study. The study took place at Mahardika Health College. The respondents consisted of 155 students in nursing, public health, midwifery, and medical record students. Students were grouped into interprofessional teams for two days and participated in IPE training consisting of lectures and small group discussions. The training is done online using the zoom meeting app. At the beginning of the first session, they completed a pre-test survey with demographic items and measures of their perception of interprofessional education to work as a team. They completed a post-test with the same measures after the end of the session. 155 students completed both the pre-test and post-test survey. The student's perception before taking ipe training is 88.38 % good to be 100% good. This study demonstrated that a short series of IPE training experiences resulted in improved perceptions of interprofessional practice.